Community Service Through Empowering The Skills Of Housewives In Utilizing Used Cooking Oil Into Multipurpose Soap In Parung Village, Parung Sub-District, Bogor. - Indrati, Briliantina Indrati; Hermawan, Andi; Susanti, Eni; Herdiansyah, Fitrah; S, Suryanih; Khofifah, Siti; Rahmatika, Riza (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2025)
Community service through collaboration to find solutions for the utilization of household waste that is useful through the Creativity Industry Seminar activity, which produces soap as a cleaning agent that is usually made from fat or oil processed with alkali, such as sodium hydroxide, and functions to bind dirt and oil so that it can be cleaned with water and has economic value and benefits as a cleaning agent soap that can be used in everyday life.